Design, synthesis, and applications of DNA–macrocyclic host conjugates. Issue 83 (26th September 2018) - Zhou, X.; Pathak, P.; Jayawickramarajah, J.
Abstract : This review discusses the nascent field of DNA–host conjugates and their applications in advanced self-assemblies, nanostructures, and input-triggered switches. Abstract : With this Feature Article we review, for the first time, the development of DNA–host conjugates—a nascent yet rapidly growing research focus within the ambit of DNA supramolecular chemistry. Synthetic hosts (such as cyclodextrins, cucurbiturils, and calixarenes) are well-suited to be partnered with DNA, since DNA assembly and host–guest binding both thrive in aqueous media, are largely orthogonal, and exhibit controllable and input-responsive properties. The covalent braiding of these two supramolecular synthons thus leads to advanced self-assemblies and nanostructures with exciting function that range from drug delivery agents to input-triggered switches. The latter class of DNA–host conjugates have been demonstrated to precisely control protein activity, and have also been used as modulable catalysts and versatile biosensors.